Peluang Indonesia sebagai Ketua ASEAN Tahun 2023 dalam Mempromosikan Penggunaan Local Currency Settlement dan QR Code Lintas Batas terkait Transaksi Perdagangan di Asia Tenggara - Fernando, Jason; Turnip, Ezra Yora (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2023)
This research aims to explain that Indonesia plays an important role in promoting the use of Local Currency Settlement and Cross-Border QR Code while holding the ASEAN chairmanship position in 2023. Local Currency Settlement functions to settle bilateral transactions between countries in one Southeast Asian region using the currencies of each of these countries. The presence of the LCS was motivated by high global inflation due to geopolitical tensions and rising US Dollar interest rates, so that this situation became an opportunity for ASEAN member countries to use local currencies. The purpose of this research is to analyze the efficiency of the LCS as a method of trade transactions in the Southeast Asia region in strengthening economic integration and reducing dependence on the US Dollar. Even the LCS is the main instrument that has the impact of strengthening currency stability in the Southeast Asian countries themselves, making export-import activities easier for each other, and creating ease in the process of foreign capital inflows into the region. In addition, Indonesia also bears more responsibility in dealing with obstacles to the promotion and use of the Cross-border QR Code as a technology that will facilitate local currency transactions for ASEAN, which is expected to be carried out properly through the systems and strategies that have been designed. In this research using qualitative analysis methods, as well as the theory of integration of economic areas according to Van Niekerk related to Indonesia's role in promoting the efficiency of LCS and Cross-border QR Code in ASEAN. This research concludes that Indonesia invites every ASEAN member to use this LCS, because it will create conditions in accordance with the theme of the 2023 ASEAN Summit, where Southeast Asia has the potential to become the epicentrum of regional economic growth from now on into the future. Keywords: ASEAN; digital economy; Indonesia; Local Currency Settlement; cross-border QR Code